Pola Etalase Pakaian Pada Fashion Store Urban Traffic Medan Menggunakan Algoritma Apriori - Kamil Erwansyah; Rudi Gunawan; Sri Kusnasari (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
A fashion store is a place where many people shop to meet their clothing needs, in a fashion store, of course, there are many dozens of types of brands that are arranged so that it may be difficult for the store to manage it with the naked eye because of the many demands from customers, making not a few items become neglected the arrangement of the place which should be the main point in a layout in a storefront because the arrangement of the clothing storefront greatly affects sales because it will affect the interest of potential buyers later. Seeing these problems, it takes a data mining application using a priori algorithm as a support for decision making in determining a good storefront pattern based on patterns and association rules formed from sales transaction data. The result of this research is a system that can systematically create a clothing storefront pattern, so that Urban Traffic Medan can analyze the material needs to be sold using an apriori algorithm.